La discriminación social desde una perspectiva psicosociológica (2012)
ABSTRACT: European public institutions are concerned about social discrimination because it erodes social cohesion and the fabric of society. This phenomenon can be approached from two perspectives, a psychosocial perspective, which highlights the cognitive mechanisms that allows that somebody understand and relate to the world and its objects; and a macrosocial perspective that accounts for the social and ideological structures that hold these mechanisms. Two empirical studies support this research. First, a comparative analysis that examines the social representations of discrimination in France and Poland; and second, a French study that examines the claims that victims of discrimination made at three agencies that fight against discrimination, a governmental agency (HALDE), an NGO (SOS Racism), and a trade union (CGT).